Pilot scale production of lipase using palm oil mill effluent as basal medium - Alam, Md. Zahangir; Ratna, Devi; Salleh, Md. Noor (2013)
Lipase noted as one of the most important enzymes which has widely industrial uses. Production of low cost enzyme using potential raw material will significantly enhance and attractive to the enzyme market. A local residue of palm oil mill effluent (POME) abundantly found and can be used as a basal medium for lipase production. The main objective of this study is to develop a scale up strategy of lipase production (300L of stirred tank bioreactor) for industrial uses. The lipase production was carried out by liquid state bioconversion of POME whereas Candida cylindracea as the microorganism. The fermentation media composition was based on the optimization from the previous study with 1%TSS based POME, 0.5% (W/V) peptone, 0.7% (V/V) Tween-80 and 2.2% inoculums. The fermentation was carried out for 48 hours at 30°C and pH 6. The results showed that maximum lipase production 5.72U/ml and 21.34 U/ml was determined with the scale up strategy of tip speed and P/V constant respectively.